Effect of layer thickness ratio on microstructure and mechanical properties of TiCN-HfN/TiCN-WC laminated ceramics. Issue 12 (15th June 2023) - Hu, Shiheng; Song, Jinpeng; Gao, Jiaojiao; Liu, Jiabao; Meng, Weiqi; Wang, Yao
Abstract: The TiCN-HfN/TiCN-WC(THTW) laminated ceramics with different layer thickness ratio were prepared by the vacuum hot-press sintering technology. The influence of the layer thickness ratio on the residual stress, microstructure, and mechanical properties of these laminated ceramics had been studied. The simulation results showed the compressive and tensile stress layers had a phenomenon of distribution alternately, and the residual compressive stress became smaller when the layer thickness ratio became larger. Cracks deflection and cracks bridging occurred during the crack propagation, and the simultaneous existence of the transgranular fracture and intergranular fracture were conducive to improving the comprehensive mechanical properties of these ceramics. With the increased of the layer thickness ratio, both the relative density and flexural strength initially increased and then decreased; the hardness of TiCN-HfN layer first decreased and then increased but the fracture toughness decreased continually. The fracture toughness and Vickers hardness of TiCN-WC layer increased constantly. When the layer thickness ratio was 0.8, the laminated ceramic obtained the best comprehensive mechanical properties: its surface hardness was 16.93 ± 0.30 GPa, its surface fracture toughness was 7.91 ± 0.12 MPa m 1/2, its flexural strength was 1293.54 ± 10 MPa, and its fracture toughness was 8.25 ± 0.08 MPa m 1/2 .